Analysis of Students Errors in Mathematical Reasoning on Geometry by Gender - Agus Setiawan; Cholis Sa'dijah (Journal of Disruptive Learning Innovation (JODLI), 2020)
The purpose of this study is to identify the reasoning male and female in solving geometry problems. Using qualitative descriptive approach, the subjects in this study were 42 male and 42 female students from two schools in the district Mesuji Lampung, Indonesia. The instrument used was a test essay consists of two problems related to geometry. The findings of this study indicate that male students have superior reasoning ability than female students. Another finding that students can make mistakes in every stage of reasoning is based on five indicators of reasoning primarily on third indicator it is perform mathematical manipulations and provide a reason or evidence to the truth of the solution, fourth indicator it is checking the validity of an argument, and fifth indicator it is draw conclusions and the first indicator and the second indicator students make a little mistake.